2015
DOI: 10.4049/jimmunol.1501458
|View full text |Cite
|
Sign up to set email alerts
|

A Complement-Optimized EGFR Antibody Improves Cytotoxic Functions of Polymorphonuclear Cells against Tumor Cells

Abstract: Complement-dependent cytotoxicity (CDC) has been suggested to be an important mechanism of action of tumor-targeting Abs. However, single unmodified epidermal growth factor receptor (EGFR)–targeting IgG1 Abs fail to trigger efficient CDC. For the current study, we generated a CDC-optimized variant of the EGFR Ab matuzumab (H425 wt) by introducing amino acid substitutions K326A/E333A (H425 mt). This Ab was then used to elucidate the impact of complement activation on the capacity of effector cells such as monon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 54 publications
(49 reference statements)
0
9
0
Order By: Relevance
“…Frustrated phagocytosis leading to tumor cell death (trogocytosis/trogoptosis) is a documented mechanism of tumor cell killing by macrophages (42) and has recently been described as PMN's major tumor cell killing mechanism (29). Individual EGFR antibodies do not trigger CDC against human tumor cells, unless they are specifically Fc engineered (43,44). However, combinations of two noncross-blocking EGFR antibodies of human IgG1 isotype were demonstrated to trigger significant CDC (25).…”
Section: Discussionmentioning
confidence: 99%
“…Frustrated phagocytosis leading to tumor cell death (trogocytosis/trogoptosis) is a documented mechanism of tumor cell killing by macrophages (42) and has recently been described as PMN's major tumor cell killing mechanism (29). Individual EGFR antibodies do not trigger CDC against human tumor cells, unless they are specifically Fc engineered (43,44). However, combinations of two noncross-blocking EGFR antibodies of human IgG1 isotype were demonstrated to trigger significant CDC (25).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, increased complement activation was seen in SCID mice compared with Nude or BALB/cJ mice [35]. Consequently, the complement-enhanced ADCC [12], [13] in peritoneal cavity may be a mechanism underlying the effects of KHK2805 in vivo . Regarding ADCC mechanisms, Srivastava et al reported that the anti-EGFR antibody cetuximab markedly enhanced the induction of Th1-polarizing cytokines such as CXCL10 (IP-10) in cancer-NK-DC cells co-culture [36].…”
Section: Discussionmentioning
confidence: 98%
“…Natsume et al found that the engineered constant Fc region as human IgG1/IgG3 chimeric isotypes with nonfucosylated oligosaccharides (113F[−f]) possess ADCC and CDC dual-enhanced cytotoxic functions [11]. This approach is expected to be useful for generating potent therapeutic antibodies, since complement-enhanced ADCC has also been suggested as a synergistic effect of ADCC and CDC [12], [13]. However, few studies have explored generating antibodies with such dual enhancement for application to cancer treatment.…”
Section: Introductionmentioning
confidence: 99%
“…CDC could be critical for demyelination in NMO lesions due to the combined production of anaphylatoxins (C3a, C4a, and C5a) and opsonins (C3b, C4b, and C1q) that recruit inflammatory cells (63), enhance polymorphonuclear-mediated ADCC (64), and facilitate phagocytosis (65) (Fig. 1).…”
Section: Nmo Lesion Pathology: Linking Astrocyte Destruction To Demyementioning
confidence: 99%